Drug utilization patterns and dosing appropriateness of antirheumatic drugs in outpatients with rheumatoid arthritis at Harapan dan Doa General Hospital, Bengkulu City, Indonesia - Juniarti, Silvia; Rahmawati, Reza; Maryanti, Evi; Handayani, Dian; Sari, Delia Komala; Sari, Dwi Dominica; Pertiwi, Reza; Oktarini, Rizki; Wulandari, Septi (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2025)
Rheumatoid arthritis (RA) is an autoimmune disease that requires long-term treatment and careful management. Inappropriate therapy may increase morbidity and mortality; therefore, appropriate drug selection and prescribing are essential to improving healthcare quality, particularly in hospital settings. This study aimed to determine the prescribing patterns of medications for patients with rheumatoid arthritis at Harapan dan Doa General Hospital in Bengkulu City. A descriptive, quantitative design was employed, utilizing a total sampling technique. The results showed that, based on drug combination patterns, most patients received triple-drug therapy (46.66%), followed by dual therapy (31.61%) and monotherapy (21.64%). The most common monotherapy was etoricoxib (8.33%), while the most frequent two-drug combination was methotrexate and methylprednisolone (11.66%). The predominant three-drug combination consisted of methotrexate, methylprednisolone, and meloxicam (15%). Based on therapeutic class, the prescribed drugs included nonsteroidal anti-inflammatory drugs (NSAIDs) (80%), corticosteroids (71.66%), disease-modifying antirheumatic drugs (DMARDs) (61.66%), and analgesics (10%). Although all prescribed drugs followed the recommended dosing guidelines, NSAIDs and corticosteroids were used more frequently than methotrexate. This pattern may reflect variations in clinical practice or differences in patient characteristics.